From Pawn Shops to Banks : The Impact of Formal Credit on Informal Households - Ruiz, Claudia (World Bank, Washington, DC, 2014)
This paper examines the effects of expanding access to credit on the decisions and welfare of households. It focuses on the entry of Banco Azteca, the first bank in Mexico targeting households from the informal sector. Panel data suggest that informal households in municipalities with Banco Azteca branches experienced several changes in their saving, credit and consumption patterns. In order to estimate the impact of Azteca's entry, the paper develops a dynamic model of household choices in which the bank is endogenously selecting the municipalities for branch openings. The analysis finds that in municipalities in which the bank entered, households were better able to smooth their consumption and accumulate more durable goods even though the overall proportion of households that save went down by 6.6 percent. These results suggest that the use of savings as a buffer on income fluctuations declines once formal credit is available. What is more, these effects vary across households. Among informal households, those who never receive formal job offers have the highest decline in saving rates. The model is also used to evaluate a legislation to cap interest rates levied by formal credit institutions. Simulations suggest that if the Mexican government were to cap the interest rate of Azteca at the rate for traditional banks, Azteca would stop operating in the poorest and least populated municipalities.